Analisis Perbandingan Algoritma Floyd-Warshall dan Dijkstra untuk Menentukan Jalur Terpendek Pada Jaringan Openflow - Ibrahim Attamimi; Widhi Yahya; Mochammad Hannats Hanafi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Software Defined Network (SDN) is network modeling that separates between control plane and data plane using Openflow protocol communication standard to connect both of them. SDN began to developed in recent years and has been widely implemented, one of them is network routing. There are two routing algorithms in this research which are Dijkstra and Floyd-Warshall. Both of these algorithms will be implemented using Mininet emulator and Ryu controller. Tests that performed in this research include parameters such convergence time, throughput, link failure, and resource usage. The result of convergence time test from this research showed Dijkstra's is superior to average of about 9,08-16,03milliseconds compared with the Floyd-Warshall with average of about 14,51-38,63milliseconds. Based on the results of throughput testing, both algorithms do not have significant differences. The Floyd-Warshall had an average throughput of 12.7-29.54Gbps while Dijkstra's had an average of about 12.89-29.22Gbps. For the test results from the Link failure, Floyd-Warshall is superior because it had a faster recovery time with average about 30.34-38.51seconds compared to Dijkstra's with average of 37.65-44.92seconds. Usage resource test showed that memory usage measurements for both algorithms share same memory, but CPU usage measurements showed the Floyd-Warshall consumes more CPU power compared to Dijkstra's.